Hospital Resilience in Three COVID-19 Referral Hospitals in Brazil - Karla Myrelle Paz de Sousa; Sydia Rosana de Araújo Oliveira; Betise Mery Alencar Sousa Macau Furtado; Ana Lucia Ribeiro de Vasconcelos; Stéphanie Gomes de Medeiros; Gisele Cazarin; Aletheia Soares Sampaio; Valéry Ridde (Taylor & Francis Group, 2023)
ABSTRACTHealth crises, such as the COVID-19 pandemic, challenge health systems in demonstrating resilience-the ability to cope with change, manage challenges, and adapt in order to retain their effectiveness. Understanding how such challenges affect and produce reactions in those involved in this response is extremely important. This study evaluated resilience in three referral hospitals in the city of Recife, Pernambuco, Brazil-one public, one private, and one philanthropic hospital-by examining the coping activities adopted by the nursing staff working on the COVID-19 frontline. A multiple case study was carried out, using a qualitative approach, triangulating data from direct observations, document analysis, and interviews with 21 nursing professionals working in management and care provision. Data were collected from April to October 2020. The interviews were transcribed and analyzed based on the resilience categories defined by Blanchet (2017): absorption capacity, adaptive capacity, and transformative capacity. Four themes were considered relevant to the objectives of this study: institutional support, access to personal protective equipment (PPE), work relationships, and fear and mental health. Adaptive capacity was demonstrated concerning the four themes analyzed, absorption capacity was demonstrated in two themes, and no transformative capacity was identified. The study highlighted that the health crisis was challenging for all the hospitals studied, regardless of their legal-administrative status. No differences were observed among them in terms of resilience.